2009
DOI: 10.1038/hr.2009.129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-fat diet feeding on hypothalamic redox signaling and central blood pressure regulation

Abstract: We examined the effect of high-fat (HF) feeding on blood pressure (BP) regulation, including hypothalamic redox signaling, as well as the changes in diurnal patterns and responses to restraint stress. Furthermore, we investigated whether HF feeding affects catecholamine and neuropeptide Y (NPY) biosynthesis in the adrenal medulla. Male obesity-prone Sprague-Dawley rats were fed with standard rat chow or 60% HF diet for 6 months. BP and heart rate (HR) were measured by telemetry, and circadian changes as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…HF diet did increase AT 1 receptor expression in both the hypothalamus and NTS in the two age groups, which corresponds with our previous findings (10). In addition, although there were agerelated differences in the upregulation of NADPH oxidase subunits (for example, hypothalamic NOX-2 and p47 subunits only elevated in young rats in response to HF feeding), NADPH oxidase activity elevated similarly in the two age groups.…”
Section: Long-term Cardiovascular Effects Of Hf Feedingsupporting
confidence: 89%
See 1 more Smart Citation
“…HF diet did increase AT 1 receptor expression in both the hypothalamus and NTS in the two age groups, which corresponds with our previous findings (10). In addition, although there were agerelated differences in the upregulation of NADPH oxidase subunits (for example, hypothalamic NOX-2 and p47 subunits only elevated in young rats in response to HF feeding), NADPH oxidase activity elevated similarly in the two age groups.…”
Section: Long-term Cardiovascular Effects Of Hf Feedingsupporting
confidence: 89%
“…Superoxide anion has been implicated in the mediation of sympathoexcitatory stimuli both in the hypothalamus and brain stem (11,17,27,44), and we have previously demonstrated that high-fat (HF) diet-induced obesity increased the expression and activity of NADPH oxidase, a major source of superoxide anion, in the hypothalamus, while antioxidant defense mechanisms remain unchanged (10). On the other hand, although aging does not increase central NADPH oxidase expression, it reduces hypothalamic expression of antioxidant enzymes such as copper-zinc superoxide dismutase and catalase, resulting in increased oxidative stress (13).…”
mentioning
confidence: 98%
“…Both glutamate and GABA also play important roles in maintaining baroreflex sensitivity. The release of glutamate could decrease blood pressure through the action of glutamate on AMPA receptors containing GluR2 [24,25] while GABA increases blood pressure by inhibiting the parasympathetic system circuit via GABA A receptors [26,27]. Our findings suggested that the protective effects of DMC on baroreflex control of heart rate could be due to the upregulation of GluR2 and a concomitant increase in synaptic transmission or neuronal excitability within the baroreceptor reflex pathway.…”
Section: Discussionmentioning
confidence: 92%
“…Similar HR dip attenuation was previously found in spontaneously hypertensive rats 21 and high-fat diet-induced hypertension. 22 In hypertensive rats, ivabradine dosed at daytime (the rat's resting phase) reverted the night-to-day HR rise to HR dip by 14.2%; whereas the night-time-dosed ivabradine did not exert this beneficial effect, as it left the undesirable HR rise unchanged. Interestingly, in line with our previous results, both daytime-dosed and night-time-dosed ivabradine exerted an antihypertensive effect.…”
Section: Introductionmentioning
confidence: 97%